PENGARUH KUALITAS SISTEM INFORMASI AKUNTANSI DAN KEAMANAN SISTEM INFORMASI AKUNTANSI TERHADAP KEPUASAN PENGGUNA (Studi Pada Perbankan Syariah di Bengkulu) - Rizky Hariyadi; Marsellina Fitri; Debby Arisandi (STIESNU Bengkulu, 2019)
Abstract The Effect of Quality Accounting Information System and Accounting Information System Security on User Satisfaction (Study on Islamic Banking in Bengkulu). The purpose of this study was to determine effect of quality accounting information system and security accounting information system on user satisfaction in Islamic banking. This research is descriptive research, the population in this study were all employees of Islamic banking in Bengkulu using a purposive sampling method totaling 60 respondents. The data collection method used was secondary and primary data with the analysis method, namely the reliability test, validity and multiple linear regression. The results showed that the quality accounting information system and the security accounting information system simultaneously had a significant effect on user satisfaction with a probability (sig) of 0.000